PEMBERITAAN PERISTIWA POLITIK PILGUB SUMATERA BARAT PERIODE 2016-2021 TINJAUAN ANALISIS WACANA KRITIS PERSPEKTIF TEUN A. VAN DIJK DALAM MEDIA ONLINE PORTAL HARIAN SINGGALANG - Jamaludin, Asep; Ermanto, Ermanto; Juita, Novia (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this study was to describe the use of texts thematic structure and text structure skematic by political news reporters in the period 2016-2021 of the gubernatorial election in West Sumatra in the daily news Singgalang as online media to expose political power . This research is qualitative . Data collection technique used SIMAK and technical notes. Data analysis was performed with descriptions perspective analysis Teun A. van Dijk . Based on the results, it can be concluded that the use of thematic text structure and text structure skematic use in political news second round of elections in the West Sumatra governor Singgalang online media , shows that political power does not exist . This phenomenon shows that the media supports both pairs of candidates , both Musli Kasim- Fauzi Bahar and Irwan pair Prayitno- Nasrul AbitÂ Kata kunci: wacana, berita pilgub, Harian Singgalang, Teun A. van